Multimodal Imaging and Clinical Features of Aortic Dissection in a Cat - Yewon Ji; Minjoo Kim; Bumseok Kim; Sang‐Ik Oh; Byungkwan Oh; Hakyoung Yoon (Veterinary Medicine and Science)
ABSTRACT An 11‐year‐old male castrated cat was presented for dyspnoea. Cardiomegaly and pulmonary oedema were identified radiographically. Echocardiography identified lesions of suspected aortic dissection consisting of a false lumen filled with echogenic material at the level of the aortic valve with aortic insufficiency. The cat developed pericardial effusion and chylothorax three months after the initial diagnosis. A computed tomography exam revealed a wall defect allowing connection between the true and beak‐, spiral‐shaped false lumen compressing the true lumen, which led to a diagnosis of aortic dissection. In addition, aortic wall calcification from the aortic root to the ascending aorta was identified. Ten weeks after the scan, the cat collapsed and died shortly after hospitalisation. The post‐mortem examination revealed full‐thickness aortic dissection of 2 mm and a beak‐shaped lumen surrounding the true lumen, consistent with computed tomography findings. A histopathologic exam revealed aortic dissection at the tunica media, myocyte hypertrophy and endocardial fibrosis. This case report describes clinical, multimodal imaging and histopathological features of aortic dissection in a cat and is the first to describe the corresponding computed tomography and post‐mortem findings. Aortic dissection should be considered as a differential diagnosis when true and false lumen is identified on echocardiographic and computed tomography tests.